Pedagogical Conditions for the Formation of Future Physical Education Specialists’ Readiness for Managerial Activity in Blended Learning - Liliia Rebukha; Ronghao Chen (Pedagogical Discourse, 2024)
The article under consideration addresses the pedagogical conditions that are conducive to the cultivation of the aptitude of prospective physical education specialists for managerial pursuits within the context of blended learning. The purpose of the article is to outline and characterize the pedagogical conditions for the above-mentioned training of future teachers. The article identifies the following priority areas for the development of modern education: the development of creative personalities; the ensuring of continuity of education for the whole population and all age groups; the integration of universal human values into education; and the orientation of education to the interests of each individual. The necessity of modernizing the training of future physical education specialists by integrating theory into pedagogical practice is emphasized. The professional development of specialists is emphasized, with particular attention paid to the comprehensive implementation of an individual and systematic approach to learning. The enhancement of the efficacy of training and professional and managerial development of students of physical education is facilitated by the effective utilization of specific pedagogical conditions in the educational process that engender motivation for the future profession, a high level of organization of teaching, the incorporation of predetermined educational technologies and teaching methods in them, and independence in the acquisition of knowledge. The implementation of pedagogical conditions ensures the formation of future physical education teachers' readiness for managerial activities, influencing their professional training as a whole and ensuring the constant updating of the educational programme. The programme is designed to equip students with a foundation in the principles of pedagogical activity, various teaching methods for physical education, and an understanding of age-appropriate psychology and pedagogy.The author expounds upon his personal interpretation of the notion of «pedagogical conditions in the field of physical education». The fundamental pedagogical conditions for the managerial activities of prospective physical education teachers are delineated and elucidated, namely the establishment of an incentivizing and value-based educational milieu in the course of blended learning for the cultivation of managerial competence in students, the engagement of physical education students in the development of contemporary curricula in the discipline through blended learning, the incorporation of state-of-the-art technical means of blended learning into the professional training of future physical education specialists for managerial activities, and the self-improvement of managerial activities of future physical education teachers through the organization and implementation of blended learning.